Analisis Profitabilitas Agroindustri Minyak Nilam di Desa Bambadaru Kecamatan Tobadak Kabupaten Mamuju Tengah : A Profitability Analysis of Patchouli Oil Agroindustry in Bambadaru Village, Tobadak District, Central Mamuju Regency - Sitti Ruqayya Marham; Dewi Sartika; Isnam Junais (Universitas Merdeka Madiun, 2023)
The purpose of this research was to determine the profitability of patchouli oil agroindustry in Bambadaru Village, Tobadaka District, Central Mamuju Regency, and to determine the sensitivity to changes in patchouli oil prices sold there. The sample taken above in this research was carried out intentionally and deliberately, namely the owner of a patchouli oil refining business in Bambadaruu Village, Tobadak District, Central Mamuju Regency. BEP (Break Even Point), sensitivity, and profitability analysis of the data used in this research is intended to analyze production costs and profitability. The results of this resesrch indicate that the patchouli oil agro-industry business in Bambadaru Village, Tobadak District, Central Mamuju Regency will break even or return to normal operations in units of BEP and BEP rupiah. So the number of BEP units used from the results of the analysis is 17 kg with a total of around Rp. 6,665,845. And for the sensitivity of the decrease in the selling price of patchouli oil by 20%, it can affect the profitability of the patchouli oil agro-industry business in Bambadaru Village, Tobadak District, Central Mamuju Regency, where the profits obtained by business owners have decreased. Which initially has a profit of Rp. 52,861,784 to Rp. 36.002.216